2008
DOI: 10.1002/ardp.200800035
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Anti‐HBV Activities Evaluation of New Ethyl 8‐Imidazolylmethyl‐7‐hydroxyquinoline‐3‐carboxylate Derivatives in vitro

Abstract: Some new ethyl 8-imidazolylmethyl-7-hydroxyquinoline-3-carboxylate derivatives have been synthesized and evaluated for their anti-hepatitis B virus (HBV) activities and cytotoxicities in HepG2.2.15 cells stable transfection with HBV. Compounds 13a, 11b, 11c, 12c, 13c, 11g, and 12g inhibited the expression of the viral antigens HBsAg or HBeAg in a low concentration, of which 11c (IC(50 )= 12.6 microM, SI = 12.4), 12c (IC(50 )= 3.5 microM, SI = 37.9), and 12g (IC(50) = 2.6 microM, SI = 61.6) showed more active a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…This molecule contains aquinoline ring and a small sulfonamide group. Previous studies also reported 2-sulfolmethyl quinolines showing anti-hepatitis B virus activity [ 38 ] and antiproliferative activity [ 39 ] against HepG2 cancer cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…This molecule contains aquinoline ring and a small sulfonamide group. Previous studies also reported 2-sulfolmethyl quinolines showing anti-hepatitis B virus activity [ 38 ] and antiproliferative activity [ 39 ] against HepG2 cancer cells in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation reaction of 4-chloro-6-fluoro-2-methylquinoline ( 6b ) with 3-chloroperbenzoic acid provided compound 9 [16], which was chlorinated with benzenesulfonyl chloride to afford 4-chloro-2-(chloromethyl)-6-fluoroquinoline ( 10 ) [17]. The reaction of 10 with substituted thiophenols or benzylthiols was carried out in the presence of potassium carbonate at 50 °C to give compounds 11a–d , which were converted into compounds 12a–d after treatment with 30% hydrogen peroxide and sodium tungstate in acetic acid [18]. Finally, target compounds 13a–h were obtained according to the same method as described for compounds 7a–f .…”
Section: Resultsmentioning
confidence: 99%
“…Most of these compounds showed good antiviral activity, and compound 51 (IC 50 = 4.7 μM, SI = 7.6) was the most potent, a highly specific inhibitor of HBV DNA replication in cell culture. 44 Meanwhile, taking compound 52 (QU-12, IC 50 = 36.8 μM, SI = 2.8) as the lead compound, Liu and coworkers 47 synthesized several new ethyl 8-imidazolylmethyl-7-hydroxyquinoline-3-carboxylate derivatives and evaluated their anti-HBV activity in vitro. Of them, compound 53 (IC 50 = 2.6 μM, SI = 61.6) exhibited the best activity for inhibiting the replication of HBV DNA.…”
Section: Quinolin-2-ones (Quinolines)mentioning
confidence: 99%
“…In 2009, a series of novel 6H- [1] benzothiopyrano ij4,3-b] quinoline derivatives were prepared and evaluated for their anti-HBV activity and cytotoxicity in human hepatoblastomaderived liver HepG2 cells by the Gong group 48 based on previous work from the literature. 44,47 The methyl group and the fluorine atom were tolerated at the 2-, 3-and 4-positions of the 6H- [1] benzothiopyrano ij4,3-b] quinoline ring, and the methyl group at the R 1 position was preferential for potent anti-HBV activity. Mannich base functionalities significantly affected the anti-HBsAg activity.…”
Section: Quinolin-2-ones (Quinolines)mentioning
confidence: 99%